BECOMING ISLAMIC RELIGIOUS EDUCATION TEACHER IN SOCIETY 5.0: PROFILES AND PROFESSIONALISM - Thoifah, i'anatut (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study is motivated by the rapid development of digital technology in the Society 5.0 era which demands Islamic religious education teachers to adapt, innovate, and strengthen their professional competence. This study uses a qualitative approach with the type of literature review research design. Purpose: This study aims to find out the profile of teachers in Islamic religious education, and explain how the professionalism of Islamic religious education teachers in the era society 5.0. Method: This study uses a qualitative approach with the type of literature review research design. Result: The results of this study show that: 1) The profile of teachers in Islamic religious education can be known by explaining what the functions, roles, positions, duties, responsibilities, and criteria of the ideal teacher in Islamic religious education; 2) Teacher professionalism in the Society 5.0 era requires teachers to have several skills as; Teacher Leadership, Driving Teacher, Digital Literacy, Communication, Emotional Intelligence, Global Citizenship, Team Working, and Problem-Solving. Conclusion: This study concludes that Islamic religious education teachers are expected to adapt to the challenges of the Society 5.0 era by not only mastering religious and pedagogical aspects, but also by strengthening digital literacy, leadership, and global competence. Professionalism of teachers in this context becomes the key to preparing students who are not only religiously devout but also competitive in a digital and globalized world.